2015
DOI: 10.1073/pnas.1501605112
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling stratifies pancreatic ductal adenocarcinomas into subtypes with distinct sensitivities to metabolic inhibitors

Abstract: Although targeting cancer metabolism is a promising therapeutic strategy, clinical success will depend on an accurate diagnostic identification of tumor subtypes with specific metabolic requirements. Through broad metabolite profiling, we successfully identified three highly distinct metabolic subtypes in pancreatic ductal adenocarcinoma (PDAC). One subtype was defined by reduced proliferative capacity, whereas the other two subtypes (glycolytic and lipogenic) showed distinct metabolite levels associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
309
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(334 citation statements)
references
References 56 publications
24
309
0
1
Order By: Relevance
“…Molecular profiling of biobank specimens, such as tissue and blood, holds significant potential to improve basic and translational research, especially when linked to clinical outcome data. OMICS technology can accelerate our understanding of pancreatic cancer on a molecular level by identifying key drivers of disease progression and biomarkers for diagnosis and targeted intervention [111][112][113][114][115][116]. In the future, the increased molecular understanding of pancreatic cancer will inevitably lead to more tailored treatment options.…”
Section: Palliation: Pain Relief Nutrition and Jaundicementioning
confidence: 99%
“…Molecular profiling of biobank specimens, such as tissue and blood, holds significant potential to improve basic and translational research, especially when linked to clinical outcome data. OMICS technology can accelerate our understanding of pancreatic cancer on a molecular level by identifying key drivers of disease progression and biomarkers for diagnosis and targeted intervention [111][112][113][114][115][116]. In the future, the increased molecular understanding of pancreatic cancer will inevitably lead to more tailored treatment options.…”
Section: Palliation: Pain Relief Nutrition and Jaundicementioning
confidence: 99%
“…By analyzing the metabolomic profile of 38 cell lines, Daemen et al [34] described 3 types of tumors: (i) a slow proliferative subtype (34%) with a low level of amino acids and carbohydrates and a long doubling time, (ii) a glycolytic subtype (27%) with a high level of intermediates from the glycolysis and serine pathways and reduced oxidative phosphorylation, and (iii) a lipogenic subtype (39%) enriched for various lipid and oxidative phosphorylation metabolites [34]. Interestingly, these subtypes overlap with the RNA classification.…”
Section: Metabolomic Pdac Subtypesmentioning
confidence: 99%
“…The sensitivity of a tumor is dependent on its metabolic type, which is determined by the preferred pathway of glucose, glycolysis, or lipogenesis. 18 It was recently shown that the cytotoxicity of melatonin in tumor cells is associated with its suppression of aerobic glycolysis. 19 However, the effect of AgNPs on tumor cell metabolism has not yet been completely determined.…”
mentioning
confidence: 99%